2023
DOI: 10.1029/2022jc019111
|View full text |Cite
|
Sign up to set email alerts
|

Wind Power Input to Ocean Near‐Inertial Waves Diagnosed From a 5‐km Global Coupled Atmosphere‐Ocean General Circulation Model

Abstract: Together with internal tides and lee waves, near-inertial waves (NIWs) are considered as a main source of the canonical 2 TW of mixing energy required to sustain the global overturning circulation (Ferrari & Wunsch, 2009;Munk & Wunsch, 1998;Wunsch & Ferrari, 2004). Investigating the wind power input to surface near-inertial motions is an important step toward quantifying the power available for interior mixing arising from wind-induced NIWs. This investigation has a long history, beginning with estimates based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This suggests that the averaged wind power on NIOs induced by TCs is largely dependent on the occurrence of TCs. Former studies identified a striped enhancement of wind power along specific tracks of TCs (Sun et al., 2021; von Storch & Lüschow, 2023). However, these studies were limited to a 1 year simulation period, which may have resulted in a more localized and fragmented representation of TC‐induced wind power on NIOs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that the averaged wind power on NIOs induced by TCs is largely dependent on the occurrence of TCs. Former studies identified a striped enhancement of wind power along specific tracks of TCs (Sun et al., 2021; von Storch & Lüschow, 2023). However, these studies were limited to a 1 year simulation period, which may have resulted in a more localized and fragmented representation of TC‐induced wind power on NIOs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Price-Weller-Pinkel model also has limitations due to initial oceanic conditions and model parameterization, which can result in an overestimation of global wind work (see Figure 10 of Plueddemann & Farrar, 2006). These model limitations is neatly illustrated by the substantial variability in the results of near-inertial currents obtained from different model results (von Storch & Lüschow, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations